Characterization of prenatal care in Brazil according to regional differences and factors associated with maternal attributes (Research, Society and Development, 2022)
The objective of the study was to analyze the coverage of prenatal care by regions in Brazil, from 2003 to 2018, and investigate maternal attributes associated with carrying out prenatal consultations. It is an ecological time series study, using data from the Live Birth Information System (SINASC). To analyze the distribution of the number of consultations, the number of consultations performed was used in the numerator and the total number of live births in the denominator. The percentage of live births with no prenatal consultations and with seven or more consultations were analyzed by generalized linear models by region and across the country as a whole. To analyze sociodemographic characteristics (maternal age, marital status, color/race, level of education), year of reference 2018, the chi-square test was used. Test significance level 5%. The percentage of cases with no consultation went from 3.21% (2003) to 1.67% (2018), while the percentage of seven consultations or more went from 51.08% (2003) to 71.15% (2018). In the period (2003-2018), the North region had a lower percentage of cases with seven or more consultations, and the South and Southeast regions had the highest percentage. Sociodemographic variables were associated with access to prenatal care, with a higher percentage of seven consultations or more among older white women, with a partner, and with twelve years or more of schooling. Despite the increase in coverage of prenatal care, regional and sociodemographic differences in access are still observed in the country and affect the quality of care for the binomial.